Central extracorporeal circulatory life support (cECLS) in selected patients with critical cardiogenic shock - Schmack, Leonie; Schmack, Bastian; Papathanasiou, Maria; Al-Rashid, Fadi; Weymann, Alexander; Pizanis, Nikolaus; Kamler, Markus; Ruhparwar, Arjang; Rassaf, Tienush; Luedike, Peter (Frontiers in Cardiovascular Medicine, 2023)
Background Percutaneous extracorporeal life support (pECLS) is increasingly applied in cardiogenic shock (CS) despite lack of evidence from randomized trials. In-hospital mortality of pECLS still reaches up to 60%, while vascular access site complications remain a shortcoming. Surgical approaches with central cannulation for ECLS (cELCS) have emerged as bail-out option. To date, no systematic approach exists that allows definition of in- or exclusion criteria for cECLS. Methods and results This single-center, retrospective, case-control study includes all patients fulfilling criteria for CS at the West German Heart and Vascular Center Essen/Germany between 2015 and 2020 who underwent cECLS (n=58), excluding post-cardiotomy patients. Seventeen patients received cECLS (29.3%) as first-line and 41 patients as second-line strategy (70.7%). Main complications leading to cECLS as second-line strategy were limb ischemia (32.8%) and ongoing insufficient hemodynamic support (27.6%). The first line cECLS cohort revealed 30-days mortality of 53.3% that was constant during follow-up. 30-days mortality of secondary cECLS candidates was 69.8% and mortality at 3-and 6-months was 79.1% respectively. Younger patients (<55 years) were more likely to exhibit survival benefit with cECLS (p=0.043). Conclusion Surgical cECLS in CS is a feasible therapy for highly selected patients with hemodynamic instability, vascular complications, or peripheral access site limitations as complementary strategy in experienced centers.